2021
DOI: 10.3390/cancers14010020
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and ncRNAs: Dangerous Liaisons in the Crosstalk between the Tumor and Its Microenvironment

Abstract: Autophagy is a fundamental cellular homeostasis mechanism known to play multifaceted roles in the natural history of cancers over time. It has recently been shown that autophagy also mediates the crosstalk between the tumor and its microenvironment by promoting the export of molecular payloads such as non-coding RNA (ncRNAs) via LC3-dependent Extracellular Vesicle loading and secretion (LDELS). In turn, the dynamic exchange of exosomal ncRNAs regulate autophagic responses in the recipient cells within the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 146 publications
0
1
0
Order By: Relevance
“…IL-6 activates autophagy through the upregulating JAK2 pathway and promotes chemotherapy resistance in colorectal cancer ( Hu et al, 2021 ). Furthermore, as promising regulators of autophagy, the non-coding RNAs, such as lncRNAs and miRNAs, can regulate therapeutic resistance in cancer cells ( Eng et al, 2021 ; Hou, Li & Dong, 2021 ; Xia et al, 2022 ). Moreover, increasing studies have confirmed that autophagy is involved in the progression and drug resistance of ovarian cancer cells ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 activates autophagy through the upregulating JAK2 pathway and promotes chemotherapy resistance in colorectal cancer ( Hu et al, 2021 ). Furthermore, as promising regulators of autophagy, the non-coding RNAs, such as lncRNAs and miRNAs, can regulate therapeutic resistance in cancer cells ( Eng et al, 2021 ; Hou, Li & Dong, 2021 ; Xia et al, 2022 ). Moreover, increasing studies have confirmed that autophagy is involved in the progression and drug resistance of ovarian cancer cells ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%